The Structure of Natural Science Theories - Kunčinas, Algirdas (Problemos, 1982)
Different views on the structure of scientific theories are considered. It is suggested to single out a theoretical system as the fundamental part of any natural science theory. Basing on the data of natural sciences the interrelations between the functions and structure of a theoretical system are observed and the process of theoretical system formation is discussed. A conclusion is drawn that in analysing the formation of a natural science theory, as well as in solving many other problems, it is possible to substitute a scientific theory for a theoretical system to provide a simpler and easier way for a fundamental solution of the problem under analysis.